Measuring TFP: Growth Accounting for the Real Sector of the Economy in the Republic of Srpska - Borović, Zoran S; Milunovic, Darko (Industrija, 2013)
ABSTRACT: This paper shows the results of research on contribution of Total Factor Productivity to the growth of the real sector in the Republic of Srpska. Total factor productivity is analytical tool which enables researchers to determine the contribution of supply-side production factors to economic growth. For the Republic of Srpska, which has a transition economy, it is a very difficult to construct a production function with stable and unbiased parameters, mostly because the lack of sufficiently long and dependable data series. Considering this, growth accounting enables us to identify the basic sources and direction of influences. The calculations that have been made enable researchers to identifies the Total Factor Productivity as the main driving force of economic growth for the real sector in the Republic of Srpska